2020
DOI: 10.1186/s12875-020-01250-6
|View full text |Cite
|
Sign up to set email alerts
|

The quality of primary care in community health centers: comparison among urban, suburban and rural users in Shanghai, China

Abstract: Objective: Following World Health Organization's initiatives to advance primary care, China put forth forceful policies including the Personal Family Doctor Contract to ensure that every family sign up with a qualified doctor in a community health center (CHC) ever since its 2009 New Health Reform. We used the Johns Hopkins-designed Primary Care Assessment Tool (PCAT) to assess primary care quality experienced by the contracted residents and compare this across different socioeconomic regions. Methods: Using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…This study also showed that the attractiveness of Beijing's community hospitals was unsatisfactory, regardless of central urban or suburban location. This result is consistent with previous findings [67,68]. In China, community hospital developments depend largely on the government's financial subsidies and competition from surrounding medical institutions.…”
Section: Scope and Attractiveness Of Community Hospital Servicessupporting
confidence: 93%
“…This study also showed that the attractiveness of Beijing's community hospitals was unsatisfactory, regardless of central urban or suburban location. This result is consistent with previous findings [67,68]. In China, community hospital developments depend largely on the government's financial subsidies and competition from surrounding medical institutions.…”
Section: Scope and Attractiveness Of Community Hospital Servicessupporting
confidence: 93%
“…Possible reasons for this effect is that the existing organization of medical resources is adequate in urban areas, and residents have been accustomed to seeing a doctor in secondary and tertiary hospitals, which leads to the proportions of the key population and seniors aged 65 years and above who have signed contracts being lower in urban areas. 25,26 This result indicated that, for those regions with abundant medical service from large hospitals, there should be more incentive measures for promoting the programs.…”
mentioning
confidence: 95%
“…The establishment of the first consultation system of general practitioners can give full play to the core role of rational allocation and effective utilisation of health resources [ 11 ]. General practitioners guide patients to seek medical treatment in a scientific and orderly manner and on-demand [ 12 ]. This also showed that under the hierarchical health system, primary healthcare and its capabilities were gradually improved.…”
Section: Discussionmentioning
confidence: 99%